Species Richness, Forest Structure, and Functional Diversity During Succession in the New Guinea Lowlands. (14th August 2014) - Whitfeld, Timothy J. S.; Lasky, Jesse R.; Damas, Kipiro; Sosanika, Gibson; Molem, Kenneth; Montgomery, Rebecca A.
Abstract Much of the world's tropical forests have been affected by anthropogenic disturbance. These forests are important biodiversity reservoirs whose diversity, structure and function must be characterized across the successional sequence. We examined changes in structure and diversity along a successional gradient in the lowlands of New Guinea. To do this, we measured and identified all stems ≥5 cm diameter in 19 0.25 ha plots ranging in age from 3 to >50 yr since disturbance. We also measured plant functional traits related to establishment, performance, and competitive ability. In addition, we examined change in forest structure, composition, species diversity, and functional diversity through succession. By using rarefaction to estimate functional diversity, we compared changes in functional diversity while controlling for associated differences in stem and species density. Basal area and species density increased with stand age while stem density was highest in intermediate secondary forests. Species composition differed strongly between mature and secondary forests. As forests increased in basal area, community‐weighted mean wood density and foliar carbon increased, whereas specific leaf area and proportion of stems with exudate decreased. Foliar nitrogen peaked in medium‐aged forests. Functional diversity was highest in mature forests, even after accounting for differences in stem and species diversity. Our study represents one of the first attempts to document successional changes in New Guinea's lowland forest. We found robust evidence that as succession proceeds, communities occupy a greater range of functional trait space even after controlling for stem and species density. High functional diversity is important for ecological resiliency in the face of global change.